2016
DOI: 10.1182/blood.v128.22.444.444
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism By Which Mutant Nucleophosmin (NPM1) Creates Leukemic Self-Renewal Is Readily Reversed

Abstract: Acute myeloid leukemia (AML) is self-renewal by immature myeloid precursors that fail to differentiate. An influential 'leukemia stem cell' model thus proposes that leukemogenic proteins augment or introduce a stem cell-like self-renewal program into cells, e.g., by upregulating signaling or transcription factors (TF) emblematic of stem cells (e.g., HOX). We investigated how the most recurrently mutated protein in AML, mutant nucleophosmin (mNPM1), causes leukemic cell expansion. The results challenge this mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Small molecule localizer c-mods such as Avrainvillamide ( Andresen et al, 2016 ) and Selinexor (KPT-330) ( Table 1 , shown and plotted in Figure 2A ) ( Gu et al, 2016 ; Brunetti et al, 2018 ; Holoubek et al, 2021 ), rescued NPM1 mislocalization, returning it to the nucleus and nucleolus, as well as restoring aspects of the gain and/or loss of function (reviewed in ( Falini et al, 2006 )). KPT-330 inhibits the interaction between mutant NPM1 and Crm1/XPO1 ( Andresen et al, 2016 ; Gu et al, 2016 ; Brunetti et al, 2018 ).…”
Section: Classification Of C-modsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small molecule localizer c-mods such as Avrainvillamide ( Andresen et al, 2016 ) and Selinexor (KPT-330) ( Table 1 , shown and plotted in Figure 2A ) ( Gu et al, 2016 ; Brunetti et al, 2018 ; Holoubek et al, 2021 ), rescued NPM1 mislocalization, returning it to the nucleus and nucleolus, as well as restoring aspects of the gain and/or loss of function (reviewed in ( Falini et al, 2006 )). KPT-330 inhibits the interaction between mutant NPM1 and Crm1/XPO1 ( Andresen et al, 2016 ; Gu et al, 2016 ; Brunetti et al, 2018 ).…”
Section: Classification Of C-modsmentioning
confidence: 99%
“…Small molecule localizer c-mods such as Avrainvillamide ( Andresen et al, 2016 ) and Selinexor (KPT-330) ( Table 1 , shown and plotted in Figure 2A ) ( Gu et al, 2016 ; Brunetti et al, 2018 ; Holoubek et al, 2021 ), rescued NPM1 mislocalization, returning it to the nucleus and nucleolus, as well as restoring aspects of the gain and/or loss of function (reviewed in ( Falini et al, 2006 )). KPT-330 inhibits the interaction between mutant NPM1 and Crm1/XPO1 ( Andresen et al, 2016 ; Gu et al, 2016 ; Brunetti et al, 2018 ). Despite the promise shown in preclinical and clinical studies ( Ranganathan et al, 2012 ; Brunetti et al, 2018 ; Abboud et al, 2020 ; Sweet et al, 2021 ), this class of compounds inhibits nuclear export for all Crm1/XPO1 substrates, raising concerns of off-target effects.…”
Section: Classification Of C-modsmentioning
confidence: 99%